Quantum Chemical QSPR Study of The Parameters Influences on Viscosity (?) for Some Aniline Derivatives - Sadiq Ismael; Sadiq Ismael (مجلة علوم ذي قار, 2019)
Quantitative Structure-Property Relationship (QSPR) analysis to viscosity (?) of 9 aniline derivatives have been conducted. The study was done by using molecular modelling of aniline compounds. The calculation was performed by the DFT method at B3PW91/6-31G (d,p) level of theory. The relationship analysis between viscosity (?) and physicochemical properties of aniline compounds was done by MLR analysis, with viscosity (?) as dependent variable and 9 independent variables to generate the equation that relates the structural features to the viscosity (? ) properties. The results show good models with four parameters linear equations. The best model predicted in this study is the four parametric regression equation (Eq. 6) In which the descriptors [Volume, T.E, surface(A) and Charge of N7] are included, with values of R2 = 0.924, F =12.169 and S = 0.517, Ra2= 0.848 which indicate that these parameters, play an important role in effect on viscosity (? )values.